Targeted Tumor Hypoxia Dual‐Mode CT/MR Imaging and Enhanced Radiation Therapy Using Dendrimer‐Based Nanosensitizers. (20th January 2020) - Fan, Yu; Tu, Wenzhi; Shen, Mingwu; Chen, Xuming; Ning, Yuesheng; Li, Junjun; Chen, Tingfeng; Wang, Han; Yin, Fangfang; Liu, Yong; Shi, Xiangyang
Abstract: The efficacy of radiation therapy (RT) is often limited by the poor response of hypoxia inside most solid tumors. The development of a theranostic nanoplatform for precision‐imaging‐guided sensitized RT for tumor hypoxia is still challenging. Herein, the creation of hypoxia‐targeted dendrimer‐entrapped gold nanoparticles complexed with gadolinium(III) (Gd‐Au DENPs‐Nit) for dual‐mode CT/MR imaging and sensitized RT of hypoxic tumors is reported. In this work, generation 5 poly(amidoamine) dendrimers are partially conjugated with Gd(III) chelator, entrapped with Au nanoparticles, and conjugated with hypoxia‐targeting agent nitroimidazole via a polyethylene glycol linker, and ending with chelation of Gd(III) and conversion of their leftover amine termini to acetamides. The designed dendrimer‐based nanohybrids with 3.2 nm Au cores exhibit an excellent X‐ray attenuation effect, acceptable r1 relaxivity (1.32 mM −1 s −1 ), and enhanced cellular uptake in hypoxic cancer cells, affording efficient dual‐mode CT/MR imaging of tumor hypoxia. Under X‐ray irradiation, the Gd‐Au DENPs‐Nit nanohybrids can produce reactive oxygen species, promote DNA damage, and prevent DNA repair, facilitating sensitized RT of hypoxic cancer cells in vitro and tumor hypoxia in vivo. The developed hypoxia‐targeted dendrimer‐based nanohybrids may be employed as both contrast agents and nanosensitizers for precision tumor hypoxia imaging and sensitized tumor RT. Abstract : Multifunctional hypoxia‐targeted dendrimer‐based nanosensitizers are developed using dendrimer nanotechnology to entrap gold nanoparticles and link chelator/Gd(III) complexes and hypoxia‐sensitive ligands. The developed dendrimer nanohybrids can be used as a contrast agent for dual‐mode computed tomography/magnetic resonance imaging of tumor hypoxia, and as a radiosensitizer to produce reactive oxygen species, promote DNA damage, and prevent DNA repair for sensitized radiotherapy of hypoxic tumors.